The judicial activism of the constitutional judge in Latin-America and Spain [El activismo judicial del juez constitucional en iberoamérica] (2020)
The concept of judicial activism is an American creation with a lot of influence in Ibero-America. Through the years, many definitions have been given to judicial activism, which merges with the expression «government by judges». The concept has been criticized lately by the doctrine due to its different meanings, despite some interpretations of the Supreme Court of the United States allowing, from the judicial perspective, to better identify the cases in which the judges are called to be activists. However, these interpretations of judicial activism must be adapted to be correctly used in the Ibero-American context, because of the particularities of social inequality, problems in the distribution of wealth and the malfunctioning of democratic mech-anisms, which varies widely in our culture. © 2020, Centro Estudios Politicos Constitucionales. All rights reserved.